Failure - Puschmann-Nalenz, Barbara (Peter Lang GmbH, 2020)
Failure regarding important goals presents a topic mostly neglected in public discussion. Yet the failure of personal relationships or professional ambitions is a common experience. Contemporary fiction addresses failing in individuals. The narratives provide the space where the awareness unfolds that disillusionment has a place in human life.
Description based on publisher supplied metadata and other sources
Keywords: Englisch; Roman; Scheitern